Pelatihan Penggunaan Sistem Informasi Inventaris Bagi Petugas Poliklinik Di Kawasan Pemulung Rangkah Surabaya - Faried Effendy; Barry Nuqoba; Army Justitia; Indah Werdiningsih (JATI EMAS (Jurnal Aplikasi Teknik dan Pengabdian Masyarakat), 2021)
The “Scavenger” polyclinic is a polyclinic that provides free medical treatment and medicine for people in the scavenger village area. From the operational side, the polyclinic is assisted by medical personnel from the Indonesian Red Crescent (BSMI) and medicines from the Al-Falah Social Fund Foundation (YDSF), while the polyclinic admin comes from residents. Based on the results of interviews and observations, it is concluded that what partners need is insight and skills in inventory activities, especially inventory management, archive and asset management, and an application that can help polyclinic administrators recapitulate assets and making weekly reports. Based on these problems, this community service activity aims to provide training and provide knowledge about the correct and optimal inventory process using the Goods Inventory Information System and also Microsoft Excel. The information system is web-based and set up offline for simplicity and flexibility. From the pre-test and post-test results, it is concluded that there has been an increase in insight and knowledge about the information system and excel material being taught.